2002
DOI: 10.1128/jvi.76.2.569-581.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Factor(s) Secreted from CD8+T Lymphocytes Inhibits Human Immunodeficiency Virus Type 1 Replication through STAT1 Activation

Abstract: CD8؉ T lymphocytes can suppress human immunodeficiency virus type 1 (HIV-1) replication by secreting a soluble factor(s) known as CD8 ؉ T-lymphocyte antiviral factor (CAF). One site of CAF action is inhibition of HIV-1 RNA transcription, particularly at the step of long terminal repeat (LTR)-driven gene expression. However, the mechanism by which CAF inhibits LTR activation is not understood. Here, we show that conditioned media from several herpesvirus saimari-transformed CD8؉ T lymphocytes inhibit, in a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 102 publications
(101 reference statements)
6
74
0
Order By: Relevance
“…Although their identities are not yet known, the mechanism of their antiviral activities points to the inhibition of transcription of viral genes (4,10). The findings presented in this study indicate that HRF blocks HIV-1 transcription through direct action on the nuclear NF-B p50/p65 dimer, preventing it from forming transcriptionally active DNA/protein complex.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although their identities are not yet known, the mechanism of their antiviral activities points to the inhibition of transcription of viral genes (4,10). The findings presented in this study indicate that HRF blocks HIV-1 transcription through direct action on the nuclear NF-B p50/p65 dimer, preventing it from forming transcriptionally active DNA/protein complex.…”
Section: Discussionmentioning
confidence: 71%
“…R ecent years brought much attention to novel mechanisms of defense against HIV-1 by both CD8 and CD4 T cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Although much of this interest was dedicated to studying the antiviral responses of CD8 T lymphocytes, it has been well known that some infected individuals mount vigorous HIV-1-specific CD4 T cells responses, resulting in the elaboration of IFN-␥ and antiviral ␤-chemokines (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the specific step in HIV-1 production that is enhanced by SOCS1, we next performed gene reporter assays using either luciferase expression constructs under the control of wildtype HIV-LTR (pLTR-luc), or a full-length provirus vector (pNL4-3-luc) (15). Interestingly, SOCS1 overexpression was found not to affect the transcription of these reporter constructs (data not shown), indicating that SOCS1 enhances HIV-1 replication via posttranscriptional mechanisms during virus production.…”
Section: Bodies (mentioning
confidence: 99%
“…15,21,22 Increasing evidence supports a role for α-defensins in inhibiting HIV-1 infection, [23][24][25][26][27][28] and several different mechanisms have been proposed, including direct activity on HIV-1 virions, inhibition of viral replication following HIV-1 entry into cells, and upregulation of CC chemokines. [25][26][27] A recent study among 23 HIV-1-infected infants suggested that increased α-defensins in breast milk collected at 1 week postpartum were associated with reduced risk of infant HIV-1 acquisition after adjusting for breast milk HIV-1 RNA. 22 To further examine associations between α-defensins and vertical HIV-1 transmission, we measured α-defensins in breast milk specimens collected from HIV-1-infected women and defined correlates of elevated α-defensins and the relationship between defensins and infant HIV-1 acquisition during 1 year of follow-up.…”
Section: Introductionmentioning
confidence: 99%